Global Factors of Transformation and Competitiveness of National Higher Education Systems in the 21st Century (Economic journal of Lesya Ukrainka Volyn National University, 2017)
The article is devoted to the analysis of opportunities and threats for the development of national higher education systems. Factors which have a global impact on the transformation and competitiveness of higher education systems in the 21st century are identified.Based on the analysis of international documents, analytical and statistical data, and methods of empirical research, a set of global demographic, socio-economic and technological factors of the competitiveness of higher education systems is systematized.The global impact of demographic factors is manifested in the reduction in the proportion of young people in Europe, including Ukraine, structural shifts in the age distribution of the population in favor of older people, and consequently - the reduction in demand for educational products among the population of traditional «student» age. Socio-economic factors are associated with the asymmetry of human development indicators and active processes of various forms of migration, global competition for talented students and researchers. Technological factors, with signs of the fourth industrial revolution, are responsible for the diversification of teaching and learning methods, the growth in the number of on-line educational products, the development of various types of non-formal education, and, as a consequence, the democratization of higher education.The originality of the research is related to the substantiation of theoretical hypotheses regarding the main tendencies and factors of the development of higher education by means of empirical analysis and a wide range of statistical, sociological and expert data.Based on the results of the empirical analysis, the opportunities and threats of the external and internal environment of its functioning are determined. The results of the analysis make it possible to determine the competitive advantages of the higher education system and its institutions at the national level, to identify their strengths and weaknesses, and, accordingly, to improve the processes of developing competitiveness management strategies in theglobal educational space.